Gambaran Kejadian Laringospasme Pada Tindakan Ekstubasi Pasca General Anestesi Di RSU Proklamasi Rengasdengklok - Nabhani Nabhani; Mustika Mustika; Lisna Shinta Dewi (Jurnal Sains dan Kesehatan, 2022)
Background: Complications that can occur during extubation include laryngospasm. Laryngospasm is an exaggerated response stimulated by the presence of blood, secretions, or surgical debris, especially when the depth of anesthesia is light. If laryngospasm is not treated properly, there is a risk of causing morbidity and mortality. Objective: To describe the incidence of laryngospasm in extubation after general anesthesia at the Proklamasi Rengasdengklok General Hospital. Method: The design in this study is descriptive quantitative, the number of samples as many as 30 respondents were taken by accidental sampling. Data collection tools used observation sheets, the data were analyzed descriptively to determine the frequency and percentage of the type of extubation and the degree of laryngospasm. Result: The most frequently used extubation technique is the deep extubation technique, which is 21 people (70%). While conscious extubation as many as 9 people (30%). While the highest degree of laryngospasm was laryngospasm degree 0 as many as 22 people (73.3%), Grade 1 as many as 6 people (20%) and degree 2 as many as 2 people (6.7%) and none of the respondents experienced grade 3 laryngospasm. Conclusion: Most of the patients at RSU Proklamasi Rengasdengklok were extubated using deep extubation technique, and the majority of patients had grade 0 laryngospasm.